Traditional knowledge as folk medicine for health care in a riverside community in the interior of the Amazon (Research, Society and Development, 2022)
This study deals with the use of traditional knowledge for health care in communities in the interior of the Amazon, specifically in the community of Arapixuna, in the municipality of Santarém, State of Pará, Brazil. The objective was to investigate the traditional medicinal practices of health care that residents of the locality. 154 medical records of users of the Family Health Strategy were evaluated, from 2018 to 2021, to verify the main diseases that occurred in the region and the existence or not of the record of their treatment, with traditional knowledge. Then, 100 individual registration forms from the Health Unit were evaluated and, from these, 21 participants were selected for the interview. It was observed in the sociodemographic profile, equivalence between females and males, age group between 54-65 years, complete high school, farming profession, family income of 1 minimum wage and Catholic religion. The profile of the interviewees showed that the majority were women aged between 31 and 40 years. Popular resources are used by the population, such as teas, baths, syrups, animal lard and massages, as well as allopathic medicines available at the Health Unit, however, traditional knowledge is the first resource used. The main health problem reported by study participants was Covid-19 flu syndrome. It is hoped that this research can contribute to new studies on the subject, fostering dialogues and reflections on care and its popular practices, passed on between generations in riverside communities in the interior of the Amazon.